Preliminary Study on the Evaluation System of Technological Innovation Index for the Central Enterprises of International First-class Enterprises. Issue 2 (February 2020) - Chang, Yan; Shi, Yongpeng
Abstract: The State-Owned Assets Supervision and Administration attached great importance to the construction of technological innovation capabilities of central enterprises, and clearly proposed to study the evaluation index system of technological innovation capabilities of central enterprises, carry out evaluation of technological innovation indexes, and guide and encourage enterprises to upgrade the level of technological innovation. Technological innovation has become a powerful driving force for continuously promoting the scientific development of central enterprises. It is of great significance for accelerating the improvement of the level of technological innovation of central enterprises to carry out the evaluation of central enterprises' technological innovation index, establish an effective mechanism to guide technological innovation of all departments, and provide scientific decision-making basis for technological innovation of central enterprises. The core of this research revolves around the technology innovation index of central enterprise for building a world-class enterprise. First, systematically sort out the characteristics of technological innovation in world-class enterprises. Second, analyze the characteristics of technological innovation of central enterprises and the shortcomings of current state-owned enterprises' technological characteristics compared with first-class enterprises. Third, build a technology innovation index evaluation system of world-class enterprises.